Body Roundness Index and Waist–Hip Ratio Result in Better Cardiovascular Disease Risk Stratification: Results From a Large Chinese Cross-Sectional Study - Li, Ying; He, Yongmei; Yang, Lin; Liu, Qingqi; Li, Chao; Wang, Yaqin; Yang, Pingting; Wang, Jiangang; Chen, Zhiheng; Huang, Xin (Frontiers in Nutrition, 2022)
Background: The appropriate optimal anthropometric indices and their thresholds within each BMI category for predicting those at a high risk of cardiovascular disease risk factors (CVDRFs) among Chinese are still under dispute. Objectives: We aimed to identify the best indicators of CVDRFs and the optimal threshold within each BMI category among Chinese. Methods: Between 2012 and 2020, a total of 500,090 participants were surveyed in Hunan, China. Six anthropometric indices including waist circumference (WC), a body shape index (ABSI), body roundness index (BRI), waist-hip Ratio (WHR), hip circumference (HC), and waist-height ratio (WHtR) were evaluated in the present study. Considered CVDRFs included dyslipidaemia, hypertension, diabetes mellitus (DM) and chronic kidney disease (CKD). The associations of anthropometrics with CVDRFs within each BMI category were evaluated through logistic regression models. The area under the receiver operating characteristic curve (AUROC) was used to assess the predictive abilities. Results: For the presence of at least one CVDRFs, the WHR had the highest AUROC in overweight (0.641 (95%CI:0.638, 0.644)) and obese (0.616 (95%CI:0.609, 0.623)) males. BRI had the highest AUROC in underweight (0.649 (95%CI:0.629, 0.670)) and normal weight (0.686 (95%CI:0.683, 0.690)) male. However, the BRI had the highest discrimination ability among the females in all BMI categories, with AUROC ranging from 0.641 to 0.727. In most case, the discriminatory ability of WHtR was similar to BRI and was easier to calculate, therefore, thresholds of BRI, WHR and WHtR for CVDRFs identification were all calculated. In males, BRI thresholds of 1.8, 3.0, 3.9 and 5.0, WHtR thresholds of 0.41, 0.48, 0.53 and 0.58, and WHR thresholds of 0.81, 0.88, 0.92 and 0.95 were identified as optimal thresholds across underweight, normal weight, overweight, and obese populations, respectively. The corresponding BRI values in females were 1.9, 2.9, 4.0 and 5.2, respectively, and WHtR were 0.41, 0.48, 0.54 and 0.59, while the WHR values were 0.77, 0.83, 0.88 and 0.90. The recommended BRI, WHtR or WHR cut-offs could not statistically differentiate high-risk CKD or hypercholesterolemia populations. Conclusions: We found that BRI and WHR were superior to other indices for predicting CVD risk factors, except CKD or hypercholesterolemia among Chinese.